The evolution of the Middle Class in Latin America - Leopoldo Tornarolli (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
Latin American countries have always been characterised by relatively high levels of income inequality, even taking into account their degree of economic development. If such 'excess inequality' is combined with the fact that these are mostly middle-income and low-income countries, it can be understood that, in general, the middle class has not historically represented a significant proportion of the population in many countries in the region. However, since the beginning of the 21st century, most countries in Latin America have enjoyed a relatively stable process of economic growth, accompanied by decreases in income inequality. This has resulted in a significant reduction in the incidence of poverty in the region and an increase in the share of the population belonging to the middle class. Currently, the size of the middle class in most countries in the region is similar to or even exceeds that of the poor population. [...]
Keywords: 330; Einkommensverteilung; Mittelschicht; Evolutionsökonomik; Wirtschaftswachstum; Lateinamerika